Environmental & architectural phenomenology. Vol. 11, issue 3 - (:unkn) unknown (Kansas State University. Architecture Department, 2000)
Vol. 11, No. 3, Fall 2000 (includes “items of interest,” "citations received,” book review of Thomas Thiis-Evensen's Archetypes of Urbanism, essay by Ingrid Leman Stefanovic, and poem by Christine Rhone).
Keywords: Environmental psychology - Periodicals; Human beings - Effect of environment on - Periodicals; Architecture - Environmental aspects - Periodicals; Architecture - Human factors - Periodicals; Architecture - Psychological aspects - Periodicals; Phenomenology - Periodicals